Quality-of-Life Outcomes in Female Patients With Ileal Conduit or Orthotopic Neobladder Urinary Diversion: 6-Month Results of a Multicenter Prospective Study - Siracusano, Salvatore; Zaka, Agustina; Bassi, Pierfrancesco; Gontero, Paolo; Mearini, Ettore; Imbimbo, Ciro; Simonato, Alchiede; Dal Moro, Fabrizio; Giannarini, Gianluca; Valotto, Claudio; Montorsi, Francesco; Colombo, Renzo; et al. (Frontiers in Oncology, 2022)
Radical cystectomy (RC) often affects patients’ life as this surgery is a traumatic and invasive event for the patients, with drwabacks on their daily, social, working and sex life. Such changes in Quality of Life (QoL) of patients are commonly studied through retrospective clinical evaluations and rarely with longitudinal studies. To date, studies focusing on functional outcomes, sexual function, and health-related QoL for female patients are lacking. We evaluated 37 patients using EORTC QLQ-C30 (QLQ-30) and Short-Form 36 (SF-36) questionnaires, before and after surgery, at 3 and 6 months of follow-up. The mean values for the emotional functioning in QLQ-C30 as well as the mental health in SF-36 were significantly higher in the ONB group compared to the IC group at 3 months follow-up. These differences were not significant at 6 months follow-up. At 6 months follow-up, the ONB group showed a higher mean score in the physical and role functioning than the IC group. Although there was a statistically significant age difference at baseline of the two groups, none of the results are correlated to age, as demonstrated by Spearman’s analysis. The ONB seems to represent the most advantageous solution compared to the IC in terms of QOL at 6-month follow-up.